Determinants of SMEs performance in Nigeria: A pilot study - Aminu, Ibrahim Murtala; Mohd Shariff, Mohd Noor (MCSER Publishing, Rome-Italy, 2015)
The objective of this research work is to examine and explore quantitatively a small sample of data on the determinants of SMEs Performance in Nigeria. The study adopted survey approach to collect 46 usable questionnaires from SMEs in Kano as one of the strata based on stratified random sampling method. The model produces six factors that are used as a determinant of SMEs performance in Nigeria. Therefore, validity and reliability of the instruments were examined through panel of expert and also the small sample of the data was analyzed using SPSS v18.Results confirmed the validity and reliability of the instruments adapted in the pilot study.